TRANSFORMATION OF THE QUALITY OF PUBLIC SERVICES UNDER THE INFLUENCE OF DIGITALIZATION - Тарнавський, Артур (SWorldJournal, 2026)
The article examines the process of transforming the quality of public services in the context of their digitalization. The qualitative changes and advantages of digitalization in the provision of such services are identified. It is substantiated that the